Digital Image Encryption by Using a Modified Hill Code - Sochif Prasetiya; Mohammad Hasan; Kiswara Agung Santoso (Jurnal ILMU DASAR, 2014)
Data security is very important data needed to stay awake in strict confidence from hacker intrusion or criminals who want to steal the data. Data security methods that are used in this paper is a digital image encryption by using a modified Hill’s code which is done by changing the way of encryption. If we are using Hill’s code then matrix pixel multiplied is the key matrix while on the modification Hill’s code before the key matrix then the matrix is multiplied pixels must be added to the results of the main diagonal elements of the matrix times key. The results obtained in the process of digital image encoding indicating that the image is encoded with password modification results of modified Hill's code more mixed reviews when compared to the image that was encoded with password Hill so that more effective in securing data in the form of a digital image. The size of the image file using the encoding results in a modification password Hill is smaller than ordinary password Hill with a percentage decrease of 4.6 % so more ease in delivery through electronic media Keyword: Digital image, modified Hill code, encryption, description